2023
DOI: 10.1101/2023.09.10.557047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Less neutralization evasion of SARS-CoV-2 BA.2.86 than XBB sublineages and CH.1.1

Yanping Hu,
Jing Zou,
Chaitanya Kurhade
et al.

Abstract: The highly mutated BA.2.86, with over 30 spike protein mutations in comparison to Omicron BA.2 and XBB.1.5 variants, has raised concerns about its potential to evade COVID-19 vaccination or prior SARS-CoV-2 infection-elicited immunity. In this study, we employ a live SARS-CoV-2 neutralization assay to compare the neutralization evasion ability of BA.2.86 with other emerged SARS-CoV-2 subvariants, including BA.2-derived CH.1.1, Delta-Omicron recombinant XBC.1.6, and XBB descendants XBB.1.5, XBB.1.16, XBB.2.3, E… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Six months after the boost, the efficacy of the sera against EG.5.1.3 and BA.2.86.1/JN.1 was barely detectable. This confirms reports indicating that these two variants are among the most immune evasive viruses described so far, even if some variations between studies have been observed 16,[21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Six months after the boost, the efficacy of the sera against EG.5.1.3 and BA.2.86.1/JN.1 was barely detectable. This confirms reports indicating that these two variants are among the most immune evasive viruses described so far, even if some variations between studies have been observed 16,[21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 89%
“…XBB.1.16.1 and EG.5.1.3 neutralization titers were the lowest (22 and 30-fold lower than BA.1, respectively). BA.2.86.1 neutralization was about 2-fold more sensitive to neutralization than EG.5.1.3, confirming recent results 16,[21][22][23][24][25][26][27][28][29][30] .…”
Section: Sensitivity Of Xbb-derived and Ba2861 Variants To Sera From ...supporting
confidence: 86%
See 1 more Smart Citation
“…Our findings indicate that the model can accurately predict the impact of new spike protein mutants on the neutralization activity of therapeutics and vaccines (R 2 = 0.77), making it a valuable tool for identifying emerging viral variants that are likely to evade current COVID-19 treatments Our model's predictions for emerging SARS-CoV-2 lineages align with current research findings. Consistent with recent data, [27][28][29] the model predicts that the newer XBB descendants, specifically EG.5, FL.1.5.1, and XBB.1.16, have significantly reduced in vitro susceptibility to both vaccines and monoclonal antibodies, rising concerns for evading vaccine-driven immunity and lack of efficacy to clinically relevant monoclonal antibodies. On further analysis of mutations linked to reduced responsiveness, our model identifies the spike mutation F456L, present in EG.5 and FL.1.5.1, as a primary contributor to reduced neutralization by selected COVID-19 antibodies and vaccines.…”
Section: Discussionsupporting
confidence: 78%
“…On August 17, 2023, the World Health Organization (WHO) designated BA.2.86, a highly mutated subvariant originating from BA.2, as a variant under monitoring due to potential immune evasion risks. However, recent studies employing live and pseudovirus neutralization assays indicate that BA.2.86 elicits a higher neutralizing antibody response to mRNA bivalent boosters than newer XBB descendants, 27,29,32 though slightly lower than its parental lineage (BA.2). Despite over 30 amino acid mutations in its spike region compared to the parental lineage (BA.2), 32 many of which are novel to both the VAE and neural network, our model accurately predicted BA.2.86's behavior, underscoring its performance in emerging lineages.…”
Section: Discussionmentioning
confidence: 97%